2013
DOI: 10.1159/000356711
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transhepatic Biliary Drainage in Patients with Postsurgical Bile Leakage and Nondilated Intrahepatic Bile Ducts

Abstract: Objective and Background: Bile leakage is a serious postoperative complication and percutaneous transhepatic biliary drainage (PTBD) may be an option when endoscopic treatment is not feasible. In this retrospective study, we established technical and clinical success rates as well as the complication rates of PTBD in a large group of patients with postoperative bile leakage. Methods: Data on all patients with nondilated intrahepatic bile ducts who underwent a PTBD procedure for the treatment of bile leakage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 29 publications
1
33
0
2
Order By: Relevance
“…As previous report, the incidence of infection after drainage in malignant obstructive jaundice is 14% -47% (De et al, 2013), cholestasis caused by biliary obstruction is advantageous to the bacteria breeding, and high bilirubin levels is easy leading to intestinal flora, intestinal mucosa barrier damage and bacterial translocation (Englesbe et al, 2005;Ozden et al, 2005). The rate of newly onset of infection after drainage reached 47.6% in our study, this infection rate is high.…”
Section: Discussionsupporting
confidence: 66%
“…As previous report, the incidence of infection after drainage in malignant obstructive jaundice is 14% -47% (De et al, 2013), cholestasis caused by biliary obstruction is advantageous to the bacteria breeding, and high bilirubin levels is easy leading to intestinal flora, intestinal mucosa barrier damage and bacterial translocation (Englesbe et al, 2005;Ozden et al, 2005). The rate of newly onset of infection after drainage reached 47.6% in our study, this infection rate is high.…”
Section: Discussionsupporting
confidence: 66%
“…Plastic stents and covered metal stent are commonly used for the drainage and relief of benign stricture of biliary and pancreatic ducts [14]. It is suggested that these stents should be removed or exchanged within 3–6 months to prevent late complications [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…[14]. There are some complications after stent insertion, such as stent occlusion, proximal or distal migration, secondary duct injury and even the failure of stent removal [58].…”
Section: Introductionmentioning
confidence: 99%
“…Typically small and asymptomatic bilomas can be monitored periodically whereas, in cases with large-sized and infected lesions, or where the patient is medically unfit for surgery, percutaneous drainage is the appropriate approach, and may suffice for the evacuation of bilomas. Adjunct therapies, including percutaneous transhepatic biliary drainage (PTBD) and an endoscopic technique, are mandatory to facilitate healing of the defect in persistent cases, and these yield satisfactory results (15,27,28). As a general rule, endoscopic intervention is responsive for perforations located distally to the confluence of the left and right hepatic duct, whereas PTBD is responsive for perforations located proximally to the confluence.…”
Section: Discussionmentioning
confidence: 99%